Fluvial to bay sequence stratigraphy and seismic facies of the Cretaceous to Paleogene successions in the MITI Sanriku‐oki well and the vicinities, the Sanriku‐oki forearc basin, northeast Japan. (15th March 2017) - Takano, Osamu; Tsuji, Takashi
Abstract: This paper describes the significant depositional setting information derived from well and seismic survey data for the Upper Cretaceous to Lower Eocene forearc basin sediments in the central part of the Sanriku‐oki basin, which is regarded as a key area for elucidating the plate tectonic history of the Northeast Japan Arc. According to the results of well facies analysis utilizing cores, well logs and borehole images, the major depositional environments were of braided and meandering fluvial environments with sporadically intercalated marine incursion beds. Seismic facies, reflection terminations and isopach information provide the actual spatial distributions of fluvial channel zones flowing in a north–south trending direction. The transgression and regression cycles indicate that the Upper Cretaceous to Lower Eocene successions can be divided into thirteen depositional sequences (Sequences SrCr‐0 to SrCr‐5, and SrPg‐1 to SrPg‐7). These depositional sequences demonstrate three types of stacking patterns: Types A to C, each of which shows a succession mainly comprising a meandering fluvial system, a braided fluvial system with minor meandering aspects in the upper part, and major marine incursion beds in the middle part, respectively, although all show an overall transgressive to regressive succession. The Type C marine incursion beds characteristically comprise bay center and tidal‐dominated bay margin facies. Basin‐transecting long seismic sections demonstrate a roll up structure on the trench slope break (TSB) side of the basin. These facts suggest that during the Cretaceous to Eocene periods, the studied fluvial‐dominated forearc basin was sheltered by the uplifted TSB. The selective occurrences of the Type C sequences suggest that when a longer‐scale transgression occurred, especially in Santonian and early Campanian periods, a large bay basin was developed, creating accommodation space, which induced the deposition of the Cretaceous Kuji Group along the arc‐side basin margin. Abstract : Fluvial sequence stratigraphy and seismic facies were analysed for the MITI Sanriku‐oki well and the vicinity in the Sanriku‐oki forearc basin, northeast Japan.